AI TOOLS FOR DEVELOPING CRITICAL THINKING AT THE LESSONS OF ENGLISH (A CASE OF READING) - Bezhina, V.V.; Solovyova, N.A. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
The rapid advancement of artificial intelligence (AI) has revolutionized educational methodologies, providing novel tools to enhance student engagement and cognitive development. This article explores how AI tools can be effectively integrated into English language lessons to cultivate critical thinking skills. By analyzing various AI–powered applications, this study highlights the benefits and challenges of using AI to foster analytical reasoning, problem–solving, and linguistic proficiency among students based on the cases in reading at 3rd year studentsof the university.
Keywords: AI; critical thinking; reading strategy; developing skills; language proficiency